EFFECTIVENESS OF VERBAL INFORMATION STRATEGY AND HAZARD EXPOSURE TECHNIQUE IN MODIFYING ADOLESCENTS ATTITUDE TOWARDS DRUG ABUSE - Ezeike, Edith; Ada, Nyamene; Nnamah, Glad (Sokoto Educational Review, 2020)
The study tested the effectiveness of Verbal Information and Hazard Exposure Technique in modifying adolescents’ attitude towards Drug Abuse. A quasi - experimental design was used. Two treatment models and one control group were used, involving non-randomized control group, pre-test, post-test design. The sample comprised of (200) hundred adolescents from two boys and two girls secondary schools in Anambra State. The instrument used for the study was researchers made questionnaire on Adolescents Attitude Towards Drug Abuse (AATDA). Data obtained were analysed using t-test statistics. The findings showed that Hazard Exposure technique is more effective than Verbal Information Strategy in modifying adolescents’ attitude towards drug abuse. Based on the findings one of the recommendations was that Counsellors Association of Nigeria and Psychology Association of Nigeria should organize workshops and seminars on drug abuse using Hazard Exposure Technique in the society.